PRE-SERVICE EFL TEACHERS' EXPERIENCE IN INTEGRATING TPACK DURING TEACHING PRACTICE PROGRAM - Pradita, Linda; Mardiana, Wiwik; Mustpa, Deni (UC Journal: ELT, Linguistics and Literature Journal, 2023)
This study explains the experience of Pre-service EFL teachers in integrating TPACK during teaching practice programs. This case study was to investigate twelve Pre-service EFL teachers in English education at the Universitas Islam Majapahit who has carried out a teaching practice program and applied technology. Data collected from their interviews, lesson plans, and teaching videos were analyzed using thematic analysis. The finding indicates that (1) Pre-service EFL teachers familiar with TPACK from its various classifications for teaching English; (2) Pre-service EFL teachers integrated TPACK for learning activities and doing assessment; (3) the contribution of TPACK for Pre-service EFL teachers during the teaching process has a positive impact on students and makes it easier Pre-service EFL teachers in administrative management.